(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study sought to determine the perception of Delta State business centre operators of ICT competencies needed for success in their business. Two research questions has guided the study. The study was a survey research and the area of study was Delta State. The population of the study consisted of 624 business centre operators registered with the ministry of commerce in Delta State. The sample for the study consisted of 375 business centre operators randomly selected from the population of the study. Structured questionnaire with 43 items used for data collection, for the study. The reliability of the instrument was determine by the use of split half method using spearman rank order of correlation while the coefficient was further computed using the spearman brown’ prophecy formula, t-test statistical tool was used for analysis of the hypotheses at 0.05 level of significance. Findings revealed that word processing and spread sheet competencies are perceived as highly required for successful operation of business centre. It was recommended among others that curriculum planners should incorporate the various competencies as perceived by Delta State business centre operators in ICT programmes both at the secondary and tertiary levels of education and that business centre operators who are deficient in the perceived competencies in word processing and spreadsheet should endeavour to acquire further training in order to achieve the required competencies for successful business centre operation.